Biomarker-guided implementation of the KDIGO guidelines to reduce the occurrence of acute kidney injury in patients after cardiac surgery (PrevAKI-multicentre): protocol for a multicentre, observational study followed by randomised controlled feasibility trial. Issue 4 (6th April 2020) - Küllmar, Mira; Massoth, Christina; Ostermann, Marlies; Campos, Sara; Grau Novellas, Neus; Thomson, Gary; Haffner, Michael; Arndt, Christian; Wulf, Hinnerk; Irqsusi, Marc; Monaco, Fabrizio; Di Prima, Ambra; et al.
Abstract : Introduction: Acute kidney injury (AKI) is a frequent complication after cardiac surgery with adverse short-term and long-term outcomes. Although prevention of AKI (PrevAKI) is strongly recommended, the optimal strategy is uncertain. The Kidney Disease: Improving Global Outcomes (KDIGO) guideline recommended a bundle of supportive measures in high-risk patients. In a single-centre trial, we recently demonstrated that the strict implementation of the KDIGO bundle significantly reduced the occurrence of AKI after cardiac surgery. In this feasibility study, we aim to evaluate whether the study protocol can be implemented in a multicentre setting in preparation for a large multicentre trial. Methods and analysis: We plan to conduct a prospective, observational survey followed by a randomised controlled, multicentre, multinational clinical trial including 280 patients undergoing cardiac surgery with cardiopulmonary bypass. The purpose of the observational survey is to explore the adherence to the KDIGO recommendations in routine clinical practice. The second phase is a randomised controlled trial. The objective is to investigate whether the trial protocol is implementable in a large multicentre, multinational setting. The primary endpoint of the interventional part is the compliance rate with the protocol. Secondary endpoints include the occurrence of any AKI and moderate/severe AKI as defined by the KDIGO criteria within 72 hours after surgery, renal recovery at day 90, use of renal replacement therapy (RRT) and mortality at days 30, 60 and 90, the combined endpoint major adverse kidney events consisting of persistent renal dysfunction, RRT and mortality at day 90 and safety outcomes. Ethics and dissemination: The PrevAKI multicentre study has been approved by the leading Research Ethics Committee of the University of Münster and the respective Research Ethics Committee at each participating site. The results will be used to design a large, definitive trial. Trial registration number: NCT03244514 .